Giraldo, J. (2019). Marx after marxism. Medellín: Editorial Universidad de Antioquia - Sánchez Marín, Leandro (Estudios de Filosofía, 2020)
The book by Jorge Giraldo, the subject of this commentary, presents a collection of texts published in various academic spaces in the last nineteen years. The author structures this reissue of his works in two well-defined parts. The first refers to some concepts of Karl Marx that have always been present at the core of studies on this thinker: politics, work, criticism, and education. In the second part, the author aims to explore the possibilities of the relationship between Marx and liberalism, more precisely between the thought of the latter and those of Immanuel Kant and John Rawls. In addition, the book ends with a brief comment on the author's journey through some places linked to Marx's biography.